Interactions between ShPP2-1, an F-box family gene, and ACR11A regulate cold tolerance of tomato. (1st July 2021) - Song, Jianwen; Shang, Lele; Chen, Shiwei; Lu, Yongen; Zhang, Yuyang; Ouyang, Bo; Ye, Zhibiao; Zhang, Junhong
Abstract: There is a critical need to identify germplasm resources and genes that promote cold tolerance of tomato because global tomato production is threatened by cold stress. We found that the expression of an F-box gene family member named ShPP2-1 from Solanum habrochaites is cold inducible and studied its contribution to cold tolerance. Overexpression of ShPP2-1 in cultivated tomato (AC) reduced cold tolerance by intensifying damage to cell membranes. To explore the underlying molecular mechanism, we conducted a yeast two-hybrid library screen and found that a protein containing ACT domain repeats named ACR11A interacts with PP2-1. Overexpression of SlACR11A in AC enhanced the cold tolerance of seedlings and germinating seeds. Cold tolerance decreased in tomato plants that overexpressed both of these genes. Additionally, we performed seed germination experiments in the cold with 177 tomato accessions and identified two alleles of SlACR11A that differ in one single-nucleotide polymorphism. We found that one of these alleles, SlACR11A G, is significantly enriched in cold-tolerant tomato plants. Taken together, our findings indicate that the combination of low expression levels of PP2-1 and high expression levels of ACR11A can promote cold tolerance. These genes may therefore serve as direct targets for both genetic engineering and improvement projects that aim to enhance the cold tolerance of tomato.